PENGARUH PERCEIVED QUALITY TERHADAP PURCHASE INTENTION PADA PAKAIAN PRISON EDITION DI LAPAS NARKOTIKA KELAS IIA BANDUNG - Azis, Muhamad Fajar; Kusmiyanti, Kusmiyanti (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The purpose of conducting this research is to find out the effect of Perceived Quality on the Purchase Intention of Prison Edition clothes produced by the Bandung Class IIA Narcotics Penitentiary. The method used in this study is quantitative by distributing questionnaires to respondents. The sample used in this study amounted to 86 respondents. From the results of data processing, it is known that Perceived Quality influences Purchase Intention, with an influence level (R-Square) of 51.8%. Keywords: Clothing Industry; Perceived Quality; Purchase Intention